Area and volume loss of the glaciers in the Ortles-Cevedale group (Eastern Italian Alps): controls and imbalance of the remaining glaciers - L. Carturan (The Cryosphere, 2013)
A widespread loss of glacier area and volume has been observed in the European Alps since the 1980s. In addition to differences among various regions of the Alps, different responses to climate change characterize neighboring glaciers within the same region. In this study we describe the glacier changes in the Ortles-Cevedale group, the largest glacierized area in the Italian Alps. We analyze the spatial variability, the drivers, and the main factors controlling the current loss of ice in this region, by comparing mean elevation changes derived from two digital terrain models (DTMs), along with glacier extents and snow-covered areas derived from Landsat images acquired in 1987 and 2009, to various topographic factors. Glacier outlines were obtained using the band ratio method with manual corrections. Snow was classified from a near-infrared image after topographic correction. The total glacierized area shrank by 23.4 ± 3% in this period, with no significant changes in the mean altitude of the glaciers. In 2009 the snowline was 240 m higher than in the 1960s and 1970s. From the snow-covered area at the end of summer 2009, which fairly represents the extent and local variability of the accumulation areas in the 2000s, we estimate that approximately 50% of the remaining glacier surfaces have to melt away to re-establish balanced mass budgets with present climatic conditions. The average geodetic mass budget rate, calculated for 112 ice bodies by differencing two DTMs, ranged from −0.18 ± 0.04 to −1.43 ± 0.09 m w.e. a−1, averaging −0.69 ± 0.12 m w.e. a−1. The correlation analysis of mass budgets vs. topographic variables emphasized the important role of hypsometry in controlling the area and volume loss of larger glaciers, whereas a higher variability characterizes smaller glaciers, which is likely due to the higher importance of local topo-climatic conditions.